2016
DOI: 10.1021/acs.energyfuels.6b01865
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Design and Characterization of High-Cetane Alkyl Diamondoid Fuels

Abstract: Four alkyl diamondoids, 1-pentyladamantane (PA), 2-butyladamantane (BA), 2-propyladamantane (2-PrA), and 2-ethyladamantane (EA), were synthesized on a preparative scale, and key fuel properties, including density, net heat of combustion, low-temperature viscosity, and derived cetane number (DCN), were measured. The fuel molecules had densities up to 17% higher than conventional jet fuel and volumetric net heats of combustion comparable to or exceeding that of the synthetic missile fuel JP-10. Remarkably, the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
36
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 35 publications
(83 reference statements)
0
36
1
Order By: Relevance
“…These compounds have high cetane index and superior diesel quality. [13] We could also analyse the ring opening selectivity, i. e. the tendency to open the central vs. a terminal ring of PHP isomers. The detailed knowledge of the structure of ring opening products allowed us in turn to rationalise the distribution of cracked products.…”
Section: Introductionmentioning
confidence: 99%
“…These compounds have high cetane index and superior diesel quality. [13] We could also analyse the ring opening selectivity, i. e. the tendency to open the central vs. a terminal ring of PHP isomers. The detailed knowledge of the structure of ring opening products allowed us in turn to rationalise the distribution of cracked products.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its high density, pure RJ‐4 has applications as a high NHOC fuel for cruise missile propulsion, [38–40] while its low volatility and high flashpoint are well suited for ramjet engines [41] . More recently, researchers have shown that RJ‐4 can be efficiently converted to 1,3‐dimethyladamantane, a thermally stable jet fuel of interest for high speed applications [42] …”
Section: Introductionmentioning
confidence: 99%
“…[41] More recently, researchers have shown that RJ-4 can be efficiently converted to 1,3dimethyladamantane, a thermally stable jet fuel of interest for high speed applications. [42] To develop a route to RJ-4 from lignocellulosic feedstocks, it was of interest to explore 2,5-hexanedione [HD (1)] as a platform chemical for the synthesis of methylcyclopentadiene [MCPD (4), Scheme 1]. Fructose can be readily converted to 5hydroxymethylfurfural (HMF) through isomerization and acid-catalyzed dehydration, followed by selective hydrogenolysis, to generate 2,5-dimethylfuran (DMF).…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that adamantane fuels derived from some reservoirs exhibit a high density and volumetric heating value, and they are regarded as one new kind of high-energy-density hydrocarbon fuel. Alkyl-substituted adamantanes are specifically attractive, as they possess good low-temperature properties …”
Section: Introductionmentioning
confidence: 99%
“…Alkyl-substituted adamantanes are specifically attractive, as they possess good lowtemperature properties. 5 1,3-Dimethyladamantane (1,3-DMA), which is an alkyl derivative of adamantanes, has satisfying density and good thermal stability. 6,7 1,3-DMA even shows higher thermal stability than JP-10 (used by U.S. Navy and Air Force), which has been considered as a new candidate of high-energy-density fuels or energetic additives for conventional fuels.…”
Section: Introductionmentioning
confidence: 99%